Yabancı para borçlarının uyarlanması - Kıraç, Kardelen (My University, 2020)
Değer ölçüsü, tasarruf ve mübadele aracı olan para, borç ilişkilerinin çoğunun konusunu oluşturur. Kırılgan ekonomilerde ülke parasının değerinin düşmesi öngörülebilir bir olgudur. Zaman içerisinde paranın satın alma gücünün farklılaşması, tarafların ödeme yükümlülüklerini daha güvenilir buldukları yabancı para birimleri üzerinden belirlemesine neden olmuştur. Sözleşmenin kurulmasından, borcun ifa zamanına kadar geçen süreçte, toplumsal, ekonomik ve politik faktörlere bağlı olarak yabancı paranın değerinde değişimler görülebilir. Öngörülemeyen bazı olaylar sonucu, yabancı paranın değeri olağanüstü ölçüde değişmiş, işlem temelinin çökmüşse, artık sözleşmenin kurulduğu sıradaki şartlarla devamını beklemek uygun olmayacaktır. Bozulan sözleşme adaletinin yeniden tesis edilebilmesi için sözleşme uyarlanacaktır. Çalışmamızın ilk bölümünde, yabancı para borcu kavramı ve yabancı para borcunun ifası üzerinde durulacak, yabancı paranın değerindeki değişimlerin sözleşmelere etkisine ilişkin genel bilgi verilecektir. Çalışmamızın ikinci bölümünde, Türk Borçlar Kanunu m. 138 çerçevesinde uyarlamanın şartları ve sonuçları incelenecektir.Çalışmamızın son bölümünde ise, Türk Parasının kıymetinin korunmasına ilişkin mevzuat bağlamında yabancı para üzerinden sözleşme yapma yasağına ilişkin düzenlemeler ele alınacaktır.

Money, which is a measure of value, a tool of savings and exchange, is the subject of most debt relations. Currency depreciation is a predictable phenomenon in fragile economies. Differentiation of the purchasing power of money over time has led the parties to determine their payment obligations in foreign currencies, which they find more reliable. During the period from the establishment of the contract until the execution of the debt, changes in the value of the foreign currency can be seen depending on the social, economic and political factors. As a result of some unforeseen events, the value of the foreign currency may have changed tremendously and the basis of the transaction may have collapsed. In such cases, it will no longer be appropriate to wait for the contract to continue with the circumstances at the time of its establishment. The contract will be adapted to restore the justice of the broken contract.In the first part of the study, the concept of foreign currency debt and performing an obligation of foreign currency debt will be examined, and general information about the effect of differentiation in the value of a foreign currency on contracts.In the second part of the study, the conditions and results of the adaptation will be examined within the framework of the Turkish Code of Obligations (article 138).In the last part of the study, the regulations on the prohibition of contracting in foreign currencies will be discussed in the context of the legislation on the protection of the value of Turkish currency.
Keywords: Civil law; debt in foreign currency; Foreign currency obligations; Hukuk; Law; Medeni hukuk; sözleşmenin uyarlanması; the adaptation of the contract; the prohibition of contracting in foreign currencies; Yabancı para borcu; yabancı para üzerinden sözleşme yapma yasağı